Endoscopic ultrasound-guided portosystemic pressure gradient measurement vs. transjugular balloon occlusion measurement in patients with cirrhosis (ENCOUNTER): A bicentric EU study - Emma Vanderschueren; Wim Laleman; Lawrence Bonne; Geert Maleux; David R. Wagner; Chyon Yeh; Andrea Calvo; Oriol Sendino; Angels Gines; Anna Baiges; Marco J. Bruno; Juan Carlos Garcia-Pagan; et al. (JHEP Reports, 2025)
Background & Aims: Patients with cirrhosis and portal hypertension are at increased risk of hepatic decompensation and liver-related mortality. While the hepatic venous pressure gradient (HVPG) is the accepted method for quantifying portal hypertension, its measurement and limited availability pose challenges. Endoscopic ultrasound-guided portal pressure gradient (EUS-PPG) provides a direct alternative. The ENCOUNTER study is the first to compare EUS-PPG to HVPG in the same patient, simultaneously. Methods: This prospective, international, bicentric study included patients referred for HVPG or transjugular intrahepatic portosystemic shunt (TIPS) placement at the University Hospital of Leuven (Belgium) and Hospital Clinic Barcelona (Spain). Patients underwent standard-of-care HVPG, followed by simultaneous HVPG and EUS-PPG measurements under propofol general anesthesia. Results: The final analysis included 21 patients with cirrhosis undergoing simultaneous HVPG and EUS-PPG measurements, of whom 15 received TIPS. Mean HVPG and EUS-PPG values under general anesthesia were comparable (11.9 ± 5.2 vs. 10.9 ± 5.6 mmHg, p = 0.2332) and showed good correlation (r = 0.74, p = 0.0001). The individual pressure components also showed a good correlation (portal vein: r = 0.85, p <0.0001; hepatic vein: r = 0.72, p = 0.0003). In patients receiving TIPS, direct transjugular portal pressure measurements demonstrated an excellent correlation with EUS-guided portal pressures (r = 0.91, p <0.0001). Technical success was achieved in all cases, with no adverse events associated with the EUS-PPG procedure. Conclusion: EUS-PPG is a reliable and safe alternative to HVPG for the direct measurement of portal pressure. However, attention must be paid to technical challenges, including the potential overestimation of EUS-guided hepatic vein pressures and the impact of general anesthesia, which may alter pressure measurements and subsequently affect risk classification. Impact and implications: The ENCOUNTER study is the first study to directly compare endoscopic ultrasound-guided portal pressure gradient (EUS-PPG) with hepatic venous pressure gradient (HVPG) in the same patients, simultaneously. EUS-PPG is a safe and reliable direct alternative to HVPG for measuring portal pressure. However, technical challenges, including the potential overestimation of EUS-guided hepatic vein pressures and the impact of general anesthesia must be considered. EUS-PPG is particularly attractive for patients with chronic liver disease who have conflicting non-invasive test results, require additional endoscopic procedures, or in cases where HVPG may underestimate true portal pressure. ClinicalTrials.gov: NCT04987034.